2016
DOI: 10.1055/s-0041-109083
|View full text |Cite
|
Sign up to set email alerts
|

International multicenter comparative trial of transluminal EUS-guided biliary drainage via hepatogastrostomy vs. choledochoduodenostomy approaches

Abstract: Background and study aims: Endoscopic ultrasound-guided biliary drainage (EUS-BD) can be performed entirely transgastrically (hepatogastrostomy/EUS-HG) or transduodenally (choledochoduodenostomy/EUS-CDS). It is unknown how both techniques compare. The aims of this study were to compare efficacy and safety of both techniques and identify predictors of adverse events. Patients and methods: Consecutive jaundiced patients with distal malignant biliary obstruction who underwent EUS-BD at multiple international cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 26 publications
4
124
1
5
Order By: Relevance
“…Hepatogastric drainage was associated with a higher risk of complications in a recent review [9] and in a recent multicenter study, where choledochoduodenostomy was also associated with shorter inpatient stay and improved stent patency [10]. On the other hand, a comparative study between the two tech-niques showed a significantly longer stent patency with hepaticogastrostomy and a lower risk of adverse events [11].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatogastric drainage was associated with a higher risk of complications in a recent review [9] and in a recent multicenter study, where choledochoduodenostomy was also associated with shorter inpatient stay and improved stent patency [10]. On the other hand, a comparative study between the two tech-niques showed a significantly longer stent patency with hepaticogastrostomy and a lower risk of adverse events [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, these stents are associated with risks of bile leakage, fistula, and stent migration [86]. Therefore, covered SEMSs have been used recently [24,57,60,62,64,85,94,[96][97][98]. In a retrospective analysis of 121 EUS-BD [94], the use of a plastic stent was significantly associated with adverse event rate (OR 4.95, P = 0.01).…”
Section: Cq6 Which Stent Is Recommended For Eus-bd?mentioning
confidence: 99%
“…Therefore, covered SEMSs have been used recently [24,57,60,62,64,85,94,[96][97][98]. In a retrospective analysis of 121 EUS-BD [94], the use of a plastic stent was significantly associated with adverse event rate (OR 4.95, P = 0.01). Although a dedicated plastic stent for EUS-BD has been developed, the rate of adverse events was 17.4% (three mild pain and one moderate bleeding) in a prospective feasibility study [67], which appeared comparable to the conventional plastic stents.…”
Section: Cq6 Which Stent Is Recommended For Eus-bd?mentioning
confidence: 99%
“…The reasons, of course, are obvious and include improved noninvasive imaging (computed tomography and magnetic resonance imaging/magnetic resonance cholangiopancreatography), and the predominant role endoscopic ultrasound (EUS) has come to play in defining pancreaticobiliary lesions because of its relative safety and its superiority over ERCP in tissue acquisition 4 5 6 7 8. Moreover, the rate of growth of therapeutic procedures has been blunted not only by the ability of EUS to access and apply therapy to the pancreas, bile duct, and gallbladder 9 10 11 12 13 but also as a consequence of studies showing no benefit for ERCP in select situations. As such, we no longer routinely undertake biliary drainage in jaundiced patients undergoing pancreatic surgery for malignancy 14.…”
mentioning
confidence: 99%